PEMBAYARAN DENDA ADAT PENYELENGGARAAN JENAZAH DATUAK (STUDI KASUS NAGARI TANJUANG BARULAK KECAMATAN BATIPUH KABUPATEN TANAH DATAR) - Yolanda Putri; Irma Suryani (Institut Agama Islam Negeri Batusangkar, 2023)
In this problem is how the process, paying customary fines for organizing Datuak's funeral and what is the view of Islamic law regarding the delay and payment of fines for organizing Datuak's funeral in Nagari Tanjuang Barulak. This type of research is field research. From the results i found first, if the people could not get a replacement for Datuak's body for 24 hours then their people had to pay the customary fines of the cabiak siriah and if their people did not want to delay the burial of Datuak's body or did not want to wait until they could get a replacement for 24 hours then their people had to pay the customary fine of cabiak siriah is 2x the amount that has been determined. Second, the payment cabiak siriah fines is paid when the batagak penghulu is held with different nominal payment provisions at each Datuak level. Third, in the view of Islamic law that the postponement of holding Datuak's funeral and the payment of customary fines for holding Datuak's funeral is not recommended by the religion which has been explained in the hadith, for this reason these customs do not meet the requirements of 'urf shahih